The Design of Adaptive Learning Model to Support the Application of Blended Learning - Riswan Riswan (Indonesian Research Journal in Education |IRJE|, 2022)
The adaptive e-learning model is a learning model that developed in blended learning in the Information Systems Project Management (ISPM) course. The development was to improve the quality of the school teachers of Informatics and Computer Management (STMIK) Nurdin Hamzah. The initial study results on the instructors by using the question lattice instrument were in four categories. They were (1) learning organizing strategies, (2) learning delivery strategies, (3) learning management strategies, and (4) learning evaluation in conventional teaching. These showed that the teaching position was in enough category. It needs to increase the teachers’ category by developing a teaching model based on adaptive e-learning to create sustainable learning. This model was expected to increase the teachers’ category and the students’ ability to understand the ISPM course. A study on this model used a descriptive methodology to get students’ responses to the developed adaptive e-learning model. The implementation of this model showed that the students’ responses were very good, and the teachers’ category had also changed from enough to good. It is expected educational institutions can develop this model as a solution during the pandemic.